Net Activism as a Process of Citizen Emancipation. A View from some Experiences of Appropriating Digital Media in Spain - Poma, Alice; Gravante, Tommaso (Razón y Palabra, 2018)
In the article, we will show how in Spain the appropriation and use of digital communication media has become another way of making politics. In our analysis, which is based on a bottom up approach - focused on individuals who have participated in this experience - we will explore how the appropriation and alternative use of media influence empowerment processes for people and social transformations, always bearing in mind that we are discussing media experiences that arise from social protest.